An Experimental Study of the Protective Effects of Chinese Medicine Compound Eye-Patch on Asthenopia - 熊瑛 万修华 李婧 李仕明 甄毅 (Chinese journal of integrative medicine, 2013)
Objective： To observe the therapeutic efficacy and the mechanism of Chinese medicine eye-patch with invigorating blood circulation and detoxification on asthenopia. Methods： A total of 180 rabbits were subjected to three tests, namely the skin microcircuiation, the microvascular regeneration in the skin and the skin temperature change, with 60 rabbits for each test. The rabbits in each test were randomly and equally divided into three groups： the normal control group was treated with physiological saline on naked back once per day, the low dose group was treated with the eye-patch on naked back for 15 min once per day, while the high dose group was treated for three times per day. Forty Hartley guinea pigs were randomly and equally divided into four groups for the muscle tone test： the normal control group was treated with physiological saline on naked back, the model group was treated without any medication, the low dose group was treated with the eye-patch on naked back for 10 min once per day, while the high dose group was treated for three times per day. All treatments were continued for 14 days until the termination of the test. The microcirculatory blood flow was observed by using a video-microscopy system. The histological sections were used to detect the microvascular regeneration by observing the expression of factor V$. The temperature changes on the skin surface were measured by using infrared thermometer, and the muscle tone was tested by the electromyography. Results： In compare with the normal or the model group, the improvement in the skin microcirculation and the blood vascular regeneration, and the decreasing in the muscle tone in low dose and high dose groups were statistically significant with confident level at P〈0.05. Conclusions： The eye-patch with invigorating blood circulation and detoxification has great enhancement in blood vascular regeneration and skin microcirculation, and great improvement in the indexes for muscle tone. The study explains certain therapeutic efficacy and mechanism of the eye-patch and shows that it could reduce the symptoms for patients with asthenopia.